Design analysis and improvement of cooler in positive-pressure explosion-proof low-speed high-capacity induction motors. (25th January 2018) - Yu, Xiwei; Meng, Dawei
Highlights: Paper studies a low-speed induction motor with the largest capacity in the world. Cooler with a special structure was designed according to the product features. The fluid and temperature fields of the cooler were simulated and analysed. We improve the cooling performance by optimizing the structure of the motor cooler. Abstract: In this paper, we study a low-speed induction motor with the largest capacity in the world. This is a positive-pressure explosion-proof motor designed to be operated in harsh environments. First, a cooler with a special structure was designed according to the product features. Then, the fluid and temperature fields of the cooler were simulated and analysed using a global coupling method. The prototype was then subjected to a temperature rise test, and the measured temperature and speed of the flow were found to be in good agreement with the calculation results. This indicated that the design of the special structure of the cooler was reasonable and that the solution method and modelling proposed in the paper were appropriate. Finally, the internal construction of the cooler was further improved to serve as a theoretical basis for future optimisation designs.